La evaluación del aprendizaje y su influencia en el comportamiento estratégico del estudiante universitario - Fermín Navaridas Nalda (Universidad de La Rioja, 2013)
The development of lines of investigation from the same educational practice is a key to be able to establish serious and rigorous proposals that allow to improve the quality of the higher education in our centers. In this frame, there are numerous studies that emphasize the strong impact of the personal factors and of the same educational context on the quality of the university learning. In agreement with all this, the present for paper centres its attention on the singular framework of the university education, with an approac on the effect of the assessment procedures of the learning on the strategies that the students adopt during their activity of study. The conclusions corroborate the influence of the assessment systems in the processes of university learning and, in last instance, in the quality of the obtained results. From this optics, the assessment of the pupils can be treated as an indicator of the quality of the education.